2020
DOI: 10.3389/fnins.2020.00090
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine Alleviated Endoplasmic Reticulum Stress via Inducing ER-phagy in the Spinal Cord of Neuropathic Pain Model

Abstract: Studies demonstrated that spinal autophagy was impaired in spinal nerve ligation (SNL) rats. However, the relationship of endoplasmic reticulum (ER) stress and ERphagy and whether dexmedetomidine (DEX) modulates ER-phagy remain unclear. In this study, male Sprague-Dawley (SD) rats and the SNL animal model were used. 4-Phenylbutyric acid (4-PBA), tunicamycin (TM), rapamycin (RAP), and 3-methyladenine (3-MA) were intrathecally administered, respectively to demonstrate the relationship of ER stress and ER-phagy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 42 publications
3
21
0
Order By: Relevance
“…These findings indicate that DEX attenuates ERS-associated apoptosis and regulates ERS via an unknown mechanism that is inhibited by 4-PBA, as reflected by the decreased expression of CHOP, GRP78 and caspase-12 at the mRNA and protein levels. Consistent results were observed in a study by Liu et al ( 26 ), in which DEX intervention led to a significant reduction in the expression level of GRP78, a marker of ERS, and to ER-phagy, while treatment with 4-PBA successfully elevated the expression of GRP78. In a study by Liu et al ( 30 ), DEX exerted a similar effect in an animal model of cerebral ischemia-reperfusion injury, decreasing the levels of CHOP and GRP78.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These findings indicate that DEX attenuates ERS-associated apoptosis and regulates ERS via an unknown mechanism that is inhibited by 4-PBA, as reflected by the decreased expression of CHOP, GRP78 and caspase-12 at the mRNA and protein levels. Consistent results were observed in a study by Liu et al ( 26 ), in which DEX intervention led to a significant reduction in the expression level of GRP78, a marker of ERS, and to ER-phagy, while treatment with 4-PBA successfully elevated the expression of GRP78. In a study by Liu et al ( 30 ), DEX exerted a similar effect in an animal model of cerebral ischemia-reperfusion injury, decreasing the levels of CHOP and GRP78.…”
Section: Discussionsupporting
confidence: 88%
“…In previous studies, DEX exhibited a protective role in the hearts of diabetic mice by interfering with ERS or autophagy, thereby suppressing IRI (6,23); however, the results were partially attributed to the diabetes context. Furthermore, researchers have focused on the study of cells other than cardiomyocytes, such as endothelial cells, under IRI or hypoxia/reoxygenation (H/R) conditions (24,25), and have examined several crucial ERS chaperones, proteins and apoptosis indicators that are produced by organs other than the heart under IRI or H/R conditions (6,(26)(27)(28)(29)(30). These studies have shown that DEX effectively regulates the function of non-cardiomyocytes and interferes with the ERS signaling pathway under these conditions.…”
Section: Dexmedetomidine At a Dose Of 1 µM Attenuates H9c2 Cardiomyocmentioning
confidence: 99%
“…[ 29 ] It was also reported that the NRS at rest was positively correlated with serum IL-6 at postoperative day 1; the NRS at walking was positively correlated with CRP at postoperative day 1 and IL-6 at postoperative day 1 to day 3. [ 31 ] Furthermore, Liu et al [ 32 ] suggested that DEX may alleviate pain via elevating endoplasmic reticulum autophagy, showing the downregulated expression of Grp78, LC3-I, p62, while upregulated expression of and FAM134B. The study of Lee et al [ 33 ] revealed that DEX may exert non-nociceptive roles by acting as an inhibitor of TRPV1 (transient receptor potential cation channel subfamily V member in the peripheral nervous system and then reducing capsaicin-induced calcium responses to block the transmission of pain signals.…”
Section: Discussionmentioning
confidence: 99%
“…Intrathecal treatment of chemical chaperones, 4-PBA and tauroursodeoxycholic acid (TUDCA), was also found to partially reverse nociceptive behaviours after SNL. 147 , 148 In the periphery, Yamaguchi et al. 142 found that BiP, XBP1, and CHOP expression was elevated in the sensory neurons as early as one day post-SNL only to recover within a week.…”
Section: Pathophysiology Impacting the Er And Mitochondriamentioning
confidence: 99%